Mediation of the total effect of cystic fibrosis‐related diabetes on mortality: A UK Cystic Fibrosis Registry cohort study. Issue 11 (16th September 2022) - Tanner, Kamaryn T.; Daniel, Rhian M.; Bilton, Diana; Simmonds, Nicholas J.; Sharples, Linda D.; Keogh, Ruth H.
Abstract: Aim: To investigate whether the effect of cystic fibrosis‐related diabetes (CFRD) on the composite outcome of mortality or transplant could act through lung function, pulmonary exacerbations and/or nutritional status. Methods: A retrospective cohort of adult cystic fibrosis (CF) patients who had not been diagnosed with CFRD were identified from the UK Cystic Fibrosis Registry ( n = 2750). Rate of death or transplant was compared between patients who did and did not develop CFRD (with insulin use) during follow‐up using Poisson regression, separately by sex. Causal mediation methods were used to investigate whether lung function, pulmonary exacerbations and nutritional status lie on the causal pathway between insulin‐treated CFRD and mortality/transplant. Results: At all ages, the mortality/transplant rate was higher in both men and women diagnosed with CFRD. Pulmonary exacerbations were the strongest mediator of the effect of CFRD on mortality/transplant, with an estimated 15% [95% CI: 7%, 28%] of the effect at 2 years post‐CFRD diagnosis attributed to exacerbations, growing to 24% [95% CI: 9%, 46%] at 4 years post‐diagnosis. Neither lung function nor nutritional status were found to be significant mediators of this effect. Estimates were similar but with wider confidence intervals in a cohort that additionally included people with CFRD but not using insulin. Conclusion: There is evidence that pulmonary exacerbations mediate the effect of CFRD on mortality but, as they are estimated to mediate less than one‐quarter of the total effect, the mechanism through which CFRD influences survival may involve other factors.